Applying hybrid problem based learning a approach in developing C2HADAM - Shahbodin, Faaizah; Badioze Zaman, Halimah; Bakar, Norasiken (Institute of Technology Management and Entrepreneurship, Universiti Teknikal Malaysia Melaka, 2007)
This paper highlights the design and development of the prototype C2HADAM, a multimedia courseware intended for the teaching and learning of the Science subject for Form Two in the Malaysian secondary schools. This prototype has been developed using the Hybrid Problem Based Learning (PBL) approach. The discussion involves the development life cycle of the software application consisting of the analysis, desin, development, implementation adn evaluation. The reseacher also highlights some of the learning theories referred to in developing C2HADAM prototype namely PBL, contextual, collaborative and constructivism. The concept of inquiry learning, contextual education, simulation, exploratory learning and student-centered learning are also incorporated in C2HADAM. this paper also aims to show some of the screen snapshots taken from C2HADAM prototype. The findings from the preliminary reliability test are also discussed.